2011
DOI: 10.1161/circulationaha.110.953653
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Function Predicts Cardiovascular Events in Primary Prevention

Abstract: Background-Biomarkers of atherosclerosis may refine clinical decision making in individuals at risk of cardiovascular disease. The purpose of the study was to determine the prognostic significance of endothelial function and other vascular markers in apparently healthy men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
5
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 339 publications
(132 citation statements)
references
References 37 publications
(30 reference statements)
4
117
5
6
Order By: Relevance
“…18 In our own research group, we have shown not only that VTI is related to cardiovascular risk factors, but that it is also predictive of long-term outcomes in low-to intermediaterisk men. 10,11,17 Although our measurement of microvascular function was less complex than the signal-averaging approach, our findings were consistent with the Framingham group. Owing to the variety of hyperaemic velocity measures using first, average, or maximum VTI, it was important to affirm that the VTI of first beat is in fact an acceptable measurement to be used as a biomarker for cardiovascular risk stratification.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…18 In our own research group, we have shown not only that VTI is related to cardiovascular risk factors, but that it is also predictive of long-term outcomes in low-to intermediaterisk men. 10,11,17 Although our measurement of microvascular function was less complex than the signal-averaging approach, our findings were consistent with the Framingham group. Owing to the variety of hyperaemic velocity measures using first, average, or maximum VTI, it was important to affirm that the VTI of first beat is in fact an acceptable measurement to be used as a biomarker for cardiovascular risk stratification.…”
Section: Discussionsupporting
confidence: 87%
“…10,11,17 In the current analysis, the first 10 beats following cuff release were measured. Further calculations were made to obtain the average and maximum VTI values from these 10 measurements.…”
Section: Ultrasound Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, there is evidence to suggest that that hyperemic blood flow responses in such vessels hold true prognostic value for predicting future cardiovascular events. 79,80 In the only study to investigate resistance artery remodeling in SCI, individuals with chronic SCI exhibited a 40-60% reduction in SFA-reactive hyperemia compared with AB individuals. 67 This far exceeds values that occur in healthy AB individuals who undergo acute 81 or chronic 82 bed rest.…”
Section: Resistance Arteries Structural Adaptationsmentioning
confidence: 99%
“…Dysfunction of endothelial cells is also the earliest event in the process of lesion formation and atherosclerosis (7 ). Various human studies have identified that measures of endothelial dysfunction may offer prognostic information with respect to vascular events (2,3,8 ).…”
mentioning
confidence: 99%